Logística reversa do lixo eletrônico: - Luz, Lara Caroline Sousa da (Universidade Federal do Tocantins, 2022)
Reverse logistics encompasses the planning, operation and control of products with the objective of enabling the collection, reuse or return of solid waste to production or transformation centers, in accordance with current legislation in Brazil, as in the case of the National Policy Solid Waste (PNRS). This article aims to present the reverse logistics of electronic waste, more precisely the way in which the disposal of cell phones and batteries is carried out in the Araguaína - TO trade. This is an exploratory research, of a qualitative nature that used the deductive method for its achievement, resulting in the fact that the companies that work with commerce and with technical assistance for cell phones in the municipality, in the majority, to be aware of the legislation and to dispose of the products for the collection carried out by a higher education institution (IES) in the city, although it is evident that if it were not for the performance of the aforementioned IES, there might have been no initiative on the part of traders and technical assistants.